TRANSFORMACIÓN ENZIMÁTICA DE LA ESTRUCTURA CRISTALINA DEL COPOLÍMERO POLIETIL-VINIL ALCOHOL (EVOH) - ARBOLEDA E., Carolina; SEGURA S., Freimar; MEJÍA G., Amanda I. (Vitae, 2009)
Changes in the crystalline structure of the copolymer poly(ethylene-co-vinyl alcohol) (EVOH) that occurs during the enzymatic fermentation system with the fungus Phanerochaete chrysosoporium were studied. This fungus has a powerful group of oxidative enzymes that had been used for several processes of environmental pollutants degradation. In order to use the enzymatic system of the fungus to improve degradation, films of the copolymer are inoculated and maintained in a solid state fermentation (SSF) system using as substrate a mixture of agroindustrial corn wastes with an initial humidity of 90%, during forty days. Analyses of the films were made at different times of fermentation. The effect on the chemical structure of the polymer was studied by using FTIR-spectroscopy with attenuated total reflection (ATR) and changes in the crystalline structure were determined by differential scan calorimetry DSC and X-ray diffraction technique. The lignin peroxidase (LiP) activity was followed by UV-spectrophotometry. We concluded that after 20 days of fermentation the copolymer has lost 50 percent of the initial crystalline structure.